2009
DOI: 10.1016/j.ccr.2009.10.015
|View full text |Cite
|
Sign up to set email alerts
|

The JAK2 Inhibitor AZD1480 Potently Blocks Stat3 Signaling and Oncogenesis in Solid Tumors

Abstract: Summary Persistent activation of Stat3 is oncogenic and is prevalent in a wide variety of human cancers. Chronic cytokine stimulation is associated with Stat3 activation in some tumors, implicating cytokine receptor-associated Jak family kinases. Using Jak2 inhibitors, we demonstrate a central role of Jaks in modulating basal and cytokine-induced Stat3 activation in human solid tumor cell lines. Inhibition of Jak2 activity is associated with abrogation of Stat3 nuclear translocation and tumorigenesis. The Jak2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
447
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 479 publications
(473 citation statements)
references
References 49 publications
(67 reference statements)
25
447
1
Order By: Relevance
“…A similar anti-tumor effect of Stat3 antisense oligonucleotides was shown in a mouse lymphoma model [79]. Effective inhibition of tumorigenic growth of many different types of cancer www.cell-research.com | Cell Research Guobin He and Michael Karin 165 npg cells transplanted into mice was observed upon treatment with AZD1480, a highly specific JAK2 inhibitor [87].…”
Section: Stat3 As a Therapeutic Target In Human Hccmentioning
confidence: 66%
“…A similar anti-tumor effect of Stat3 antisense oligonucleotides was shown in a mouse lymphoma model [79]. Effective inhibition of tumorigenic growth of many different types of cancer www.cell-research.com | Cell Research Guobin He and Michael Karin 165 npg cells transplanted into mice was observed upon treatment with AZD1480, a highly specific JAK2 inhibitor [87].…”
Section: Stat3 As a Therapeutic Target In Human Hccmentioning
confidence: 66%
“…To verify that Jak2 and Stat5a/b are critical for Prl induction of EMT in PC cells, we used pharmacological and genetic tools to disrupt Jak2 and Stat5a/b signaling. The Jak2 kinase inhibitor, AZD1480, 64 previously shown to inhibit Stat5a/b signaling in PC cells, 38 suppressed Prl regulation of Jak2 phosphorylation (Supplemental Figure S1A) and E-cadherin, N-cadherin, vimentin, and Twist1 ( Figure 1C 5) and inoculated s.c. into the flanks of nude mice after 24 hours. After 3 weeks, cell surface E-cadherin and nuclear Stat5a/b levels were analyzed by immunohistochemistry (IHC) in paraffin-embedded tissue sections.…”
Section: Jak2-stat5a/b Signaling Induces Expression Of Emt Markers Inmentioning
confidence: 89%
“…DU145 cells are a model of androgen receptor (AR) negative and androgen-independent prostate cancer. Furthermore, unlike the AR-dependent LNCaP cells, DU145 cells have constitutive activation of both STAT3 and NF-kB (30,44,45). These cells represent also a good model of prostate tumors characterized by concomitant upregulation of ESE1/ELF3 and sustained activation of NF-kB (35).…”
Section: Ec-70124 Inhibits Nf-kb and Stat3 In Prostate Cancer Cellsmentioning
confidence: 99%
“…Inhibition of NF-kB and STAT3 individually is known to affect proliferation of DU145 cells (30,44,46,47). Given the ability of EC-70124 to block concomitantly both signaling pathways, we examined the compound's effect on the phenotype of DU145 cells.…”
Section: Ec-70124 Affects Proliferation Of Prostate Cancer Cellsmentioning
confidence: 99%